Chief Justice of Samoa launches mediation rules - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2013)
In this post on the Kluwer Mediation Blog, the launch of Samoa’s Mediation Rules 2013 by His Honour Patu Tiava’asue Falefatu Sapolu is presented.